2022
DOI: 10.3389/fpubh.2022.917390
|View full text |Cite
|
Sign up to set email alerts
|

Associations of physical activity with cognitive function and daily physical function among Chinese individuals with heart disease: A cross-sectional study

Abstract: BackgroundTo investigate the associations between different dimensions of physical activity (PA), cognitive function, and daily physical function in Chinese individuals with heart disease.Materials and methodsThis study included 2,792 individuals from the China Health and Retirement Longitudinal Study conducted in 2015. Physical activity (PA) was divided into vigorous PA (VPA), moderate PA (MPA), and light PA (LPA). Linear and logistic regression models were established to assess the associations among the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The other sociodemographic factors in this study were not significantly associated with trajectory patterns of cognitive function in our sample. Several studies have reported that women and physical activity were significantly associated with declining trajectories of cognitive function (Dong et al, 2022; Shin & Cho, 2023). Accordingly, considering cultural diversity, we require multicenter studies to determine how the sociodemographic characteristics of older adults with cardiovascular diseases affect their cognitive function over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other sociodemographic factors in this study were not significantly associated with trajectory patterns of cognitive function in our sample. Several studies have reported that women and physical activity were significantly associated with declining trajectories of cognitive function (Dong et al, 2022; Shin & Cho, 2023). Accordingly, considering cultural diversity, we require multicenter studies to determine how the sociodemographic characteristics of older adults with cardiovascular diseases affect their cognitive function over time.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, many older adults with cardiovascular disease showed a cognitive decline, reportedly due to chronic or intermittent cerebral hypoperfusion and altered cerebrovascular response (Moore & Jefferson, 2021). Previous studies have reported that older adults with cardiovascular diseases are more likely to have cognitive decline (Dong et al, 2022; Moore & Jefferson, 2021), which can lead to treatment failure by nonadherence to self‐management such as taking medication, regular exercise, and healthy diet (Lovell et al, 2019). Consequently, it is crucial to prevent and manage cognitive decline in older adults with cardiovascular diseases because it can improve their quality of life and reduce mortality (Zuo & Wu, 2022).…”
Section: Introductionmentioning
confidence: 99%